Peran Manajemen Perkantoran dalam Meningkatkan Kualitas Pelayanan Administrasi - Adelia, Nabila; Amin Ikhlasul Amal; Hasfi Fiqri Hidayah (Jurnal Budi Pekerti Agama Islam, 2025)
Office management is a key component in ensuring the effectiveness and efficiency of administrative services in both public and educational institutions. The increasing demands for service speed, accuracy, transparency, and professionalism necessitate an integrated and adaptive office management system. This study aims to explore how office management contributes to enhancing administrative service quality through a library research approach. Data were obtained from academic journals, theses, institutional reports, and theoretical literature. The analysis reveals that effective office management encompasses structured planning, proper document management, digital information systems, and staff competency development, all of which contribute significantly to improved service quality. Moreover, standard operating procedures and the integration of manual and digital systems enhance consistency and service reliability. The study supports the theoretical proposition that office management functions planning, organizing, actuating, and controlling are directly correlated with administrative performance indicators. Practical implications include the urgency of digitizing records, implementing standardized workflows, and continuously training administrative personnel. Limitations of this research lie in its purely conceptual and literature-based nature, thus future studies are recommended to adopt empirical or mixed methods approaches for broader generalizability. These findings reaffirm the importance of repositioning office management from a support function to a strategic pillar in administrative service improvement efforts.